Otra visión de los políticos “riojanos” contemporáneos. Caricatura, prensa e imagen pública (Berceo, 2024)
Berceo nº 187 is a monographic volume coordinated by Jesús Movellán Haro focused on political caricature, satirical press, and visual culture related to contemporary Riojan politicians of the 19th and 20th centuries. The publication examines how images and caricatures helped shape political discourse, collective identities, and social imaginaries through different media such as newspapers, photographs, illustrated prints, and matchbox labels. The volume includes seven scholarly studies devoted to political figures linked to La Rioja, including Espartero, Sagasta, Olózaga, Amós Salvador, and Eduardo Barriobero, approached from the perspectives of cultural history, political iconography, and visual analysis.